2003
DOI: 10.1016/j.hep.2003.09.029
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation controls the responsiveness of hepatoma cells to leukemia inhibitory factor

Abstract: The related members of the interleukin 6 (IL-6) family of cytokines, IL-6, leukemia inhibitory factor (LIF), and oncostatin M, act as major inflammatory mediators and induce the hepatic acute phase reaction. Normal parenchymal liver cells express the receptors for these cytokines, and these receptors activate, to a comparable level, the intracellular signaling through signal transducer and activator of transcription (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…In previous studies conducted in numerous normal or transformed cells, such as hepatoma cells, gp130 or OSMRb downregulations were rarely observed, in contrast to the LIFRa gene that was frequently epigenetically silenced (Blanchard et al, 2002(Blanchard et al, , 2003. In stage III melanoma, both LIFRa and OSMRb were found frequently downregulated, but only the OSMRb recruitment correlated with OSM-mediated growth inhibition.…”
Section: Osm Receptor Expression In Melanomamentioning
confidence: 74%
See 3 more Smart Citations
“…In previous studies conducted in numerous normal or transformed cells, such as hepatoma cells, gp130 or OSMRb downregulations were rarely observed, in contrast to the LIFRa gene that was frequently epigenetically silenced (Blanchard et al, 2002(Blanchard et al, , 2003. In stage III melanoma, both LIFRa and OSMRb were found frequently downregulated, but only the OSMRb recruitment correlated with OSM-mediated growth inhibition.…”
Section: Osm Receptor Expression In Melanomamentioning
confidence: 74%
“…Indeed, these inhibitors can induce expression of several epigenetically silenced tumor suppressor genes, resulting in cell cycle arrest and differentiation (Jaenisch and Bird, 2003;Blanchard and Chipoy, 2005). Our data indicated that the promoters for gp130 or LIFRa can be epigenetically silenced in normal or transformed cells, concomitant with a defect in receptor expression and STAT signaling (Blanchard et al, 2002;Blanchard et al, 2003).…”
Section: Waf1mentioning
confidence: 76%
See 2 more Smart Citations
“…There was no evidence from our own demethylation experiments in epithelial tumor cell lines in vitro [4].…”
Section: Introductionmentioning
confidence: 64%